2003
DOI: 10.1002/cb.112
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐cultural assessment of attitudes regarding perceived breaches of ethical conduct by both parties in the business‐consumer dyad

Abstract: Recent initiatives in business curricula have included emphases on global business and ethics. Using 28 scenarios which reflect potential concerns regarding the conduct of either business or a consumer, this research combines these issues by comparing the ethical predisposition of business students in Australia with their Canadian counterparts. A sample of 264 students indicated that students in both countries generally hold high expectations for the behaviour of business and consumers. Both groups exhibited q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…It would be of value to probe further into the origins of these differences of looking at marketing. In connection with this, we note that there is evidence of cross‐country differences in public attitudes towards marketing both at a normative ideological level (e.g., Dalsace and Markovitch, ) and with respect to more functional, day‐to‐day scenarios of marketing ethics (Fisher et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…It would be of value to probe further into the origins of these differences of looking at marketing. In connection with this, we note that there is evidence of cross‐country differences in public attitudes towards marketing both at a normative ideological level (e.g., Dalsace and Markovitch, ) and with respect to more functional, day‐to‐day scenarios of marketing ethics (Fisher et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…For instance, internalization moral identity has been found to positively influence deontological and utilitarian moral judgments (Conway & Gawronski, ) and ethical beliefs (McFerran, Aquino, & Duffy, ). Further, research has found that moral judgment disposition (measured in various ways; Brady & Wheeler, ; Fisher, Woodbine, & Fullerton, ; Forsyth, , ; McFerran et al, ; Schminke, ) and moral sensitivity (Morton et al, ) positively relate to moral reasoning and ethical judgments.…”
Section: Review Of Empirical Research On the Moral Selfmentioning
confidence: 99%
“…Researchers have also documented the choice of purchasing counterfeit goods in relation to the evaluation of product attributes, such as brand and logo (Gentry et al, 2001;Hoe et al, 2003). Many researchers have investigated consumer ethical decision making related to demographic characteristics, including age, gender, cultural background, and religiosity (Callen and Ownbey, 2003;Cheung and Prendergast, 2006;Fisher et al, 2002;Shen and Dickson, 2001;Swaidan et al, 2003Swaidan et al, , 2006Van Kenhove et al, 2003;Vitell and Paolillo, 2003). Of particular relevance to this study, previous research suggests that younger consumers are more likely than older consumers to engage in unethical behavior such as the purchasing of counterfeit goods (Callen and Ownbey, 2003;Cheung and Prendergast, 2006).…”
Section: Consumer Misbehaviormentioning
confidence: 99%